(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: The use of intensive educational methods Today, the use of intensive educational methods helps to understand the text process and make fun.True selected methods teach students to independent, free thinking, research, creatively approach every issue, feel the responsibility.This process requires pedagogical and psychological skills from the teacher.In this article, methods and recommendations provide for students to increase their interest and motivation.